Pembuatan bahan ajar berbasis android untuk pembelajaran fisika pada materi gelombang bunyi, gelombang cahaya dan alat optik di kelas XI SMA/MA - Muhammad Arif; Festiyed Festiyed; Desnita Desnita; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2019)
The 2013 curriculum emphasizes a learning process that is student-centered, active, interactive and integrated with a scientific approach. One supporting factor for the creation of learning is the availability of good learning resources. However, the reality in the field of learning resources used is not in accordance with the demands of the 2013 curriculum, does not meet the needs of students, and does not fully meet the criteria for good teaching materials. Teaching material used in the form of printed teaching materials that contain subject matter and questions only, without the scientific approach that includes it. Teaching materials that utilize technology are still in separate forms such as videos, animations, images, which have not been packaged in a single unit (not yet interactive). Therefore, it is necessary to design teaching materials that utilize technology such as Android on smartphones. This study aims to produce products in the form of android-based teaching materials for learning physics in sound wave material, light waves and valid optical devices. This research focuses on making an Android-based teaching material product in the form of an interactive module in accordance with the steps of making teaching material in the form of a module according to the Ministry of National Education (2010). Like the planning stage, the preparation phase (determining teaching material, type of software, models and storyboards) as well as the preparation of teaching material. The validity of the product was assessed by three physics lecturers from FMIPA UNP and one physics teacher at SMAN 8 Padang. Based on research that has been done, produced a product in the form of teaching materials based on Android. This teaching material contains text, sound, animation, music, and video. The research product was also categorized as very valid in terms of the content of teaching materials, grammar, graphics, scientific approaches and software utilization with an average value of 89.11%.